Automated lighting design in the classroom - Widya Pratama, I Putu Eka; Soehartanto, Totok; Ari Wibowo, Daniel Dany; Tjandra, Nabiilah Aziizah; Nizar, Mochammad (Bulletin of Electrical Engineering and Informatics, 2024)
Lamp automation is utilized to adjust the lighting in the classroom by adjusting to the level of sunlight intensity outside the classroom. The light intensity will be adjusted to the utilization of lights as indicated by the need to enlighten a room. Therefore, this research aims to depict the design of a light intensity measurement system using a BH1750 sensor that will be carried out to measure the intensity of sunlight in units of light (lux). The signal from the sensor will be transmitted to a mini pc which functions to process measurement data and display it on the graphical user interface (GUI). As a result, the sensor will instruct the dimmer as an actuator to control the classroom lights according to the lighting from the sun. This system is already installed in the classroom and can save energy around 35 kWh a year.